2022
DOI: 10.3390/polym14142930
|View full text |Cite
|
Sign up to set email alerts
|

A Silica–Lignin Hybrid Filler in a Natural Rubber Foam Composite as a Green Oil Spill Absorbent

Abstract: Oil spills in the marine environment are a rising concern due to their adverse impacts on living creatures and the environment. Hence, remediation methods have been used to remove the oil from the contaminated water. A sorbent material is considered the best method for oil spill absorption. However, commonly used commercial sorbents are made from nonrenewable and nonenvironmentally friendly materials. In this research, natural rubber foam (NRF) was used as a sorbent material with the addition of a filler, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…There are also other research works on surface modifications of polyurethane using various chemical moieties and nanomaterials for enhanced oil absorption reported [ 68 , 69 , 70 , 71 , 72 , 73 ]. There are several recent research works reported in the development of polymer foams for oil–water separations, which elucidates the potential of these foams as promising agents for removing oil from water bodies [ 74 , 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are also other research works on surface modifications of polyurethane using various chemical moieties and nanomaterials for enhanced oil absorption reported [ 68 , 69 , 70 , 71 , 72 , 73 ]. There are several recent research works reported in the development of polymer foams for oil–water separations, which elucidates the potential of these foams as promising agents for removing oil from water bodies [ 74 , 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we focused our attention on sorption and the chemical–physical parameters that affect this methodology [ 14 ]. Sorbent can be divided into two categories: synthetic and natural [ 15 , 16 ]. Synthetic sorbents such as rubbers, membranes, foams and aerogels are generally made from non-renewable chemicals, and they possess low or no tendency to biodegradation in natural conditions [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, carbon black (CB) has been used as a reinforcing filler in NR foams 6 . Rubber foams are commonly used in several industries such as automotive, construction and footwear, especially for applications requiring cushioning, insulation or vibration dampening 7–9 . The production of CB, as a petroleum‐based material, requires a high amount of energy leading to environmental issues and costs 10 .…”
Section: Introductionmentioning
confidence: 99%
“…NR foams with various hybrid (silica−lignin) filler contents were prepared by Mardiyati et al . as ‘green’ oil absorbents 7 . The minimum torque (125%), scorch time (102%), optimum curing time (52%), cell size (33%) and expansion ratio (23%) all increased with increasing filler concentration from 3 to 9 phr.…”
Section: Introductionmentioning
confidence: 99%